School Improvement and Safety Plan for Limited Face-to-Face Classes - L. Gildo, Desiree; R. Bermundo, Richard; M. Rociento, Margie; Christy Valencia, Marline; Anthony Eva, Mark; B. Barayoga, Lanie; L. Landicho, Lea; Jeffrey B. Boneo III, Eliseo; Albero, Imelda (PT. BATARI EDU CALYA, 2023)
As public schools nationwide in the country take a huge step of reintroducing face-to-face classes amidst pandemic and the public health situation, the study investigated the school improvement and safety plan for the limited face-to-face classes of eighty-nine (89) randomly selected public schools from Divisions of Camarines Sur and Albay, both elementary and secondary schools for the school year 2021-2022 and assessed how they effectively implemented the plan. The study utilized the descriptive-survey research method and conducted from February – July 2022. The data were collected using a developed survey questionnaire and analyzed using descriptive statistics. Results showed that the implementation of safety protocols and standards in public schools during the start of the school year was evident as they were prepared and organized prior to the conduct of classes. It is also revealed that safety protocols and standards were in consonance with the mandates of the Department of Health and observed among the public schools. Thus, it was concluded that public schools conducted and effectively implemented as per observed from the results of the school improvement and safety plans and protocols for limited face-to-face classes.